VRU-to-Truck Collision Compatibility - Cao, Jieer; Mo, Zhetong (My University, 2017)
Pedestrian safety is an important concern for truck collision compatibility development. Numerical crash simulation is widely used for truck design today and some numerical pedestrian dummy and human models are available for injury prediction in pedestrian collision simulations. A study of the collision between pedestrian and new truck front with an ideal spring system based on MADYMO has been carried out by Volvo Truck. The result shows that with this spring system, the number of pedestrian sustaining MAIS2+ injuries can be reduced potentially by up to 20%. One of this thesis work’s objectives is to compare the results between the MADYMO Ellipsoid 50th percentile male human model simulations previously done, with LS-DYNA 50th percentile male Autoliv IA pedestrian dummy model simulations. The other target is to develop a honeycomb structure to replace this simplified spring system for future industry market. The same collision scenarios as previous MADYMO study, including the truck model and different postures of pedestrian model, were constructed and simulated in LS-DYNA. The result shows that in primary impact, the deformable neck of IA model is potential to cause more severe head and neck injury than that of Ellipsoid model. Instead, the deformable arm of IA model has positive effect on reducing head injury in truck collisions. After that, six finite element (FE) plastic honeycomb structure models were developed to replace the spring system. The material of this honeycomb is Zytel® ST811HS NC010 and the thickness and length for different honeycombs were selected by FE bench test simulations aiming for similar yield force levels as in the spring systems. The result shows that this honeycomb structure performs well since 90% of the injury values’ absolute difference in low impact speed (truck speed, 24km/h) collisions and 81% in high impact speed (truck speed, 40km/h) collisions compared to reference value in spring system collisions are smaller than 20%. The stiffness of honeycomb becomes larger in high impact speed collision is the potential reason for worse performance in high speed collisions. In the future, injury caused by secondary impact needs to be further studied. The rigid truck front surface may also need to be evolved to be deformable for future design.
Keywords: Livsvetenskaper; Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Teknisk mekanik; Farkostteknik; Life Science; Transport; Sustainable Development; Innovation & Entrepreneurship; Applied Mechanics; Vehicle Engineering